2008
DOI: 10.5194/angeo-26-2081-2008
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced ion acoustic lines due to strong ion cyclotron wave fields

Abstract: Abstract. The Fast Auroral Snapshot Explorer (FAST) satellite detected intense and coherent 5-20 m electric field structures in the high-latitude topside auroral ionosphere between the altitudes of 350 km and 650 km. These electric fields appear to belong to electrostatic ion cyclotron (EIC) waves in terms of their frequency and wavelengths. Numerical simulations of the response of an electron plasma to the parallel components of these fields show that the waves are likely to excite a wave-driven parallel ion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…Observations by Michell and Samara (2010) and Ekeberg et al (2010) indicate the presence of high electric fields during the reported events as well. Bahcivan and Cosgrove (2008) suggested a mechanism for ion cyclotron waves, in the vicinity of arcs with strong electric fields and shear, to excite enhanced levels of ion acoustic fluctuations and produce enhanced backscatter in incoherent scatter experiments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Observations by Michell and Samara (2010) and Ekeberg et al (2010) indicate the presence of high electric fields during the reported events as well. Bahcivan and Cosgrove (2008) suggested a mechanism for ion cyclotron waves, in the vicinity of arcs with strong electric fields and shear, to excite enhanced levels of ion acoustic fluctuations and produce enhanced backscatter in incoherent scatter experiments.…”
Section: Discussionmentioning
confidence: 99%
“…spectrally uniform radar power enhancements, caused by increased incoherent backscatter cross section driven by ionsolitary waves. Bahcivan and Cosgrove (2008) proposed a model for NEIALs based on observations of ion cyclotron waves in the vicinity of arcs with strong electric fields observed with the FAST satellite. In this model the ion acoustic instability is driven by the ion cyclotron waves.…”
Section: Introductionmentioning
confidence: 99%
“…Another different mechanism to enhance the ion acoustic line is proposed by Forme (1993), where through a two step wave-wave interaction process a beam driven instability generates growing Langmuir waves that can decay into ion acoustic waves and opposite propagating Langmuir waves. A more recent theory proposed by Bahcivan and Cosgrove (2008) postulates that ion acoustic waves can be destabilized through a twostep process, where Electrostatic Ion Cyclotron (EIC) waves can produce non-Maxwellian electron distribution function, which creates inverse Landau damping (assuming the ions are Maxwellian). Only the Langmuir decay (Forme, 1993) and the EIC-electron distribution interaction (Bahcivan and Cosgrove, 2008) models can explain the simultaneous enhancement of both shoulders in the ion acoustic line.…”
Section: Introductionmentioning
confidence: 99%
“…A more recent theory proposed by Bahcivan and Cosgrove (2008) postulates that ion acoustic waves can be destabilized through a twostep process, where Electrostatic Ion Cyclotron (EIC) waves can produce non-Maxwellian electron distribution function, which creates inverse Landau damping (assuming the ions are Maxwellian). Only the Langmuir decay (Forme, 1993) and the EIC-electron distribution interaction (Bahcivan and Cosgrove, 2008) models can explain the simultaneous enhancement of both shoulders in the ion acoustic line.…”
Section: Introductionmentioning
confidence: 99%
“…The enhanced backscatter can reach several orders of magnitude above the thermal backscatter and is thought to occur due to enhanced levels of ion acoustic wave activity (e.g., Sedgemore-Schulthess and St. Maurice, 2001). Explanations of the physical cause of NEIALs include streaming instabilities (Rietveld et al, 1991;Wahlund et al, 1992), decay from electrostatic ion-cyclotron waves (Bahcivan and Cosgrove, 2008), and Langmuir turbulence (e.g., Forme, 1993;Guio and Forme, 2006) driven by electron beams. Observations of NEIALs reported in recent years favors the Langmuir turbulence as a model to describe the echoes.…”
Section: Introductionmentioning
confidence: 99%